2014
DOI: 10.1097/ccm.0000000000000025
|View full text |Cite
|
Sign up to set email alerts
|

B-Type Natriuretic Peptide and Risk of Acute Kidney Injury in Patients Hospitalized With Acute Coronary Syndromes*

Abstract: In patients hospitalized with acute coronary syndromes, B-type natriuretic peptide levels measured at admission are associated with acute kidney injury as well as its severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…Our study extends the finding of that study and suggests that preoperative NT-proBNP is independently associated with AKI in patients undergoing mixed types of non-cardiac surgery. This result is in accordance with observations in previous studies showing that NT-proBNP/BNP concentrations were associated with risk of AKI after cardiac surgery [19] and in other acute care settings [14][15][16][17][18].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study extends the finding of that study and suggests that preoperative NT-proBNP is independently associated with AKI in patients undergoing mixed types of non-cardiac surgery. This result is in accordance with observations in previous studies showing that NT-proBNP/BNP concentrations were associated with risk of AKI after cardiac surgery [19] and in other acute care settings [14][15][16][17][18].…”
Section: Discussionsupporting
confidence: 93%
“…Because the incidence of AKI after non-cardiac surgery is relatively low, and because conventional risk factors have good prediction performance for postoperative AKI, even biomarkers with an independent association with AKI (such as BNP) may not improve the discrimination ability of existing clinical models [17]. Despite these challenges, in our study, NT-proBNP offered modest but statistically significant improvements in the AUC, the continuous and categorical NRI, and the IDI.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…A substudy of HORIZONS-AMI, [14] including a total of 979 patients, found an independent predictive value of brain natriuretic peptide (BNP) for CI-AKI after PCI. Similarly, Moltrasio et al [26] and Akgul et al [27] also identified BNP level at admission as being associated with CI-AKI and its severity. Although BNP level correlates with NT-proBNP level, NT-proBNP levels are more stable and sensitive than BNP levels because of a longer half-life.…”
Section: Discussionmentioning
confidence: 90%
“…They found that BNP was associated with AKI as well as its severity in patients with ACS. 28 However, these studies reported BNP instead of NT-pro-BNP levels. NT-pro-BNP levels may have analytical advantages over BNP, given the enhanced stability due to a longer half-life, which allows for increased accumulation and potentially greater sensitivity for detecting more subtle structural and functional changes.…”
Section: Discussionmentioning
confidence: 99%